Immunomodulatory effect of PLGA-encapsulated mesenchymal stem cells-derived exosomes for the treatment of allergic rhinitis - Shahzad, Khawar Ali; Wang, Zhao; Li, Xuran; Li, Jiaojiao; Xu, Maoxiang; Tan, Fei (Frontiers in Immunology, 2024)
Allergic rhinitis (AR) is an upper airway inflammatory disease of the nasal mucosa.Conventional treatments such as symptomatic pharmacotherapy and allergen-specific immunotherapy have considerable limitations and drawbacks. As an emerging therapy with regenerative potential and immunomodulatory effect, mesenchymal stem cell-derived exosomes (MSC-Exos) have recently been trialed for the treatment of various inflammatory and autoimmune diseases. In order to achieve sustained and protected release of MSC-Exos for intranasal administration, we fabricated Poly(lactic-co-glycolic acid) (PLGA) micro and submicron particles encapsulated MSC-Exos (PLGA-Exos) using mechanical double emulsion for local treatment of AR. Preclinical in vivo imaging, ELISA, qPCR, flow cytometry, immunohistochemical staining, and multiomics sequencing were used for phenotypic and mechanistic evaluation of the therapeutic effect of PLGA-Exos in vitro and in vivo. The results showed that our PLGA platform could efficiently encapsulate and release the exosomes in a sustained manner. At protein level, PLGA-Exos treatment upregulated interleukin (IL)-2, IL-10 and IFN-γ, and downregulated IL-4, IL-17 and antigen-specific IgE in ovalbumin (OVA)induced AR mice. At cellular level, exosomes treatment reduced helper T cells (Th)2 cells, increased regulatory T cells (Tregs), and reestablished Th1/Th2 balance. At tissue level, PLGA-Exos significantly attenuated the infiltration of immune cells (e.g., eosinophils and goblet cells) in nasal mucosa. Finally, multiomics analysis discovered several signaling cascades, e.g., peroxisome proliferator-activated receptor (PPAR) pathway and glycolysis pathway, that might mechanistically support the immunomodulatory effect of PLGA-Exos. For the first time, we present a biomaterial-facilitated local delivery system for stem cell-derived exosomes as a novel and promising strategy for AR treatment.